'We have rights to designs': interrogating design pirating on the Ghanaian textiles market. Issue 1 (2nd January 2020) - Darku, Esther N. D.; Lubisi, Nombulelo
Abstract: This paper examines the challenges of copyright implementation in the Ghanaian textile market. Specifically, the paper looks at the challenges of administering copyright law in an informal market structure governed by both cultural norms and legal precepts. Using qualitative data collected from interviews and documents, this paper argues that copyright laws do not adequately take into account the normative systems that govern the production of textile as a cultural good. Therefore, challenges faced by the state to regulate piracy in the textile market exist because of the gap between formal legal provisions for conducting business and informal norms and market practices. The paper concludes that the copyright law in its current form does not address the normative practices at the core of trading textiles and that piracy can be effectively controlled if copyright laws incorporate cultural ideas and definition of design, authorship and ownership in the textile industry.